Online Narcotics Trafficking: a New Threat to Crime and a Challenge for Low Enforcement - Mustopa, Idad Rais (Activa Yuris: Jurnal Hukum, 2024)
Globalization is inevitable today, and in this era all aspects of human life have changed. This is marked by easy access to communication, trade, transportation and others. However, the rapid development of technology can also be used as a gap for irresponsible people in carrying out their actions, one of which is narcotics trafficking through the help of technology and online media. And with this case also involves the role of many parties and with this method the perpetrators can also minimize the level of arrest by the authorities. Research that aims to increase public awareness to be more vigilant in seeing everything, the method used in this research is qualitative by sourcing from books, journals, legal regulations and internet websites related to the research theme. Then with this research it is hoped that it will become a reference material for law enforcers in preventing and sanctioning every party involved and in this case it also requires seriousness from the Government so that similar cases do not recur in the future